EFEKTIVITAS MODEL PEMBELAJARAN IMAJINATIF TERHADAP KEMAMPUAN SISWA MENULIS TEKS CERITA PENDEK DI KELAS IX SMP RK FR XAVERIUS NAMORAMBE - Parman Marbun, Edi; Sitanggang Gusar, Martua Reynhat; Simanjuntak, Harlen (Universitas Islam Sumatera Utara, 2024)
The imaginative learning model is a learning model that invites students to express all their ideas, opinions, imagination or imagination into written form. Writing short stories is very important in student learning in class IX using the Imaginative learning model. It is hoped that the imaginative learning model can be used as fully as possible in developing students' interest in learning, especially in making short stories and making students active and creative in class by maximizing the empowerment of their minds. This research uses quantitative experimental methods, this method seeks to collect and interpret data in a precise, measurable, reasonable and systematic manner. The results of research that has been carried out on learning to write short story texts using an imaginative learning model, which occurs in the learning process makes it easier for students to understand the material and student learning outcomes increase. The reason is that students imagine more and express their ideas so that the learning they do attracts students' attention and influences students' interest in learning and students give each other opinions obtained from each other's observations and learning is more active. Apart from that, students are also supported by the motivation provided by the teacher. This can be proven from the results of hypothesis testing and data analysis that has been carried out to obtain tcount ttable.